2014
DOI: 10.1016/j.celrep.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 Controls DNA Replication Timing in Yeast through the PP1 Phosphatase Glc7

Abstract: The Rif1 protein, originally identified as a telomere-binding factor in yeast, has recently been implicated in DNA replication control from yeast to metazoans. Here, we show that budding yeast Rif1 protein inhibits activation of prereplication complexes (pre-RCs). This inhibitory function requires two N-terminal motifs, RVxF and SILK, associated with recruitment of PP1 phosphatase (Glc7). In G1 phase, we show both that Glc7 interacts with Rif1 in an RVxF/SILK-dependent manner and that two proteins implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
234
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(262 citation statements)
references
References 35 publications
25
234
2
1
Order By: Relevance
“…However, the fact that we observe large numbers of MCMs loaded at late-replicating telomeres (Fig. 1A) suggests that heterochromatin can delay the firing of loaded MCMs, perhaps by counteracting the activity of rate-limiting activators (Hiraga et al 2014;Mattarocci et al 2014).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the fact that we observe large numbers of MCMs loaded at late-replicating telomeres (Fig. 1A) suggests that heterochromatin can delay the firing of loaded MCMs, perhaps by counteracting the activity of rate-limiting activators (Hiraga et al 2014;Mattarocci et al 2014).…”
Section: Discussionmentioning
confidence: 87%
“…In budding yeast, proximity to telomeric heterochromatin is both necessary and sufficient to delay origin firing (Ferguson and Fangman 1992). This effect is regulated by Rif1-dependent recruitment of protein phosphatase I, which may antagonize origin activation by the cyclin-and DBF4-dependent kinases (Lian et al 2011;Davé et al 2014;Hiraga et al 2014;Mattarocci et al 2014). Chromatin structure-in particular, histone deacetylation by Sir2 and Rpd3-also affects the timing of nontelomeric origins (Knott et al 2009(Knott et al , 2012Peace et al 2014;Yoshida et al 2014).…”
mentioning
confidence: 99%
“…It was recently reported that Rif1 can erase Mcm2-7 phosphorylation by recruiting the protein phosphatase PP1 to the replisome. Therefore, rif1Δ suppressed a cdc7-1 mutation at 30°C and restored cell growth at that temperature (54,57,58). To investigate whether there was a correspondence between suppression of DDK mutants by rif1Δ and restoration of PFA, we first performed growth analysis and confirmed that rif1Δ could suppress a cdc7-1 mutation at 30°C but not at 37°C (Fig.…”
Section: Deletion Of the Inhibitory Domain In The N-terminal Region Omentioning
confidence: 99%
“…A recent structural study revealed a tetrameric structure of the ScRif1 C-terminal domain (27), Cdc7-mediated phosphorylation events (11,13,28).…”
mentioning
confidence: 99%